Light‐weight group signatures with time‐bound membership. Issue 7 (30th October 2015) - Malina, Lukas; Hajny, Jan; Zeman, Vaclav
Abstract: This paper presents a novel privacy‐preserving cryptographic protocol for secure many‐to‐one communication systems, for example, data collection systems, data gathering systems, vehicular networks, smart‐grids, and so on. The proposed solution provides message authenticity, integrity, and non‐repudiation, while message senders are anonymous and untraceable. The protocol is based on group signatures with a time‐bound membership. The protocol is designed to achieve efficiency on the client side where restricted devices are usually employed. On the other hand, the verification of many messages is efficient as well. Common group signature schemes offer the verification phase that needs some pairing operations and employs a long revocation list. Generally, the revocation list grows until scheme parameters and keys are recomputed. However, the reinitialization of all keys and parameters is not practical in large‐scale communication systems. By applying the optimization techniques on the group signature scheme, the verification phase becomes more efficient, and the expiration of group member secret keys naturally reduces the length of a revocation list. In addition to the full cryptographic description, we implement the proposed protocol and outline the performance results. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This paper presents a novel privacy‐preserving cryptographic protocol for secure many‐to‐one communication systems. The protocol is based on group signatures with a time‐bound membership. The protocol employs batch verification and is designed to achieve efficiency.